KONTRIBUSI KONDISI FISIK TERHADAP KEMAMPUAN SMASH PADA PERMAINAN BOLAVOLI SISWA SMA NEGERI 19 MAKASSAR - Munandar, Wahyu (Jurnal Penjaskesrek, 2017)
This research aimed to find the answer of the problems: (1) is there any explosive power contribution, arm explosive power, and wrist flexibility of ability to smash the volleyball? (2) is there any contribution of arm power explosion, explosive power of the legs, and flexibility of the wrist of ability to smash the volleyball? (3) Is there any contribution of the formation of the wrist, explosive power of the legs, and arm power of ability to smash the volleyball in game? (4) is there any explosive power of the legs, arm power explosion, wrist joints together of ability to smash the volleyball in game?.The type of this research was descriptive with three independent variables and one dependent variable. The populations and samples were the students of SMA Negeri 19 Makassar, with random sampling got the samples as many 30 students. Data analysis technique used single regression test and multiple regression test at a significant level 95%. Based on the result of data analysis, It can be concluded that: (1) there is a significant contribution of explosive power of the legs to smash the volleyball, where the value ß = 0.635, with the value of  to = 4.353 (P < 0,05), and the contribution = 40.40%, (2) there is a significant contribution of arm power explosion to smash the volleyball, where the value ß = 0.648, with the value of to= 4.505 ( p< 0.05 ), and the contribution = 42.00 %, (3) there is a significant contribution of wrist stretching to smash the volleyball, where the value ß = 0.534, with the value of to = 3.343 (P < 0,05, with the contribution = 28.50%, (4) there is a significant contribution of explosive power of the legs, arm power explosion, wrist joints together of ability to smash the volleyball, where Ro = 0.673 with  R2 = 0.453 (P < 0,05), with the  contribution 45.30%.